Ḥizb al-‘Adālah wa al-Rafāhīyah (PKS) wa Siyāsāt al-Huwīyah al-Islāmīyah: Istiratijīyāt Kawādir al-Ḥizb li Ta’ṭīr Qaḍāyā Nukhabihim al-Fasādīyah al-Mālīyah - Rangga Eka Saputra (Studia Islamika, 2016)
This article explains the mechanism of cadre engagement and militancy of Prosperous Justice Party (PKS), as the Islamist party in Indonesia. This study departs from the puzzle that despite their president, Luthfi Hasan Ishaaq, was accused for corruption crime ahead of elections in 2014, but the PKS’s vote still stable from the previous election period (2009). Since PKS is a party cadre, this study argues that the success of the PKS in maintaining the vote in the 2014 election was because of militancy and loyalty of their cadre in doing work collectively for the party. By using the framing approach in the field of social movement, this study concludes that the engagement and militancy of the PKS’s cadre have been influenced by their vigorous framing resources both ideology and identity, as well as the ability of party leaders in mobilizing those resources to their cadre at the lower levels.DOI: 10.15408/sdi.v23i2.3313